The Relationship between the Body Mass Index and Different Education Times in Secondary Schools - Karadeniz, Soner; Can, Sema (Asian Journal of Education and Training, 2019)
The aim of this study was to investigate the relationship between body mass index (BMI) and educational periods in secondary school students. The study was conducted on 832 students, 418 girls (Mage: 12.99±.83) and 414 boys (Mage: 12.92±.85), who received dual and full-time education in the centre of Sivas Province. As data collection tool, BMI was calculated by measuring weight and height, and the percentile curve developed by Neyzi et al. (2008) in the classification of obesity and underweight was used. As the statistical analysis, the mean, standard deviation, frequency, percent values were used for descriptive statistics of all variables and Pearson Chi Square test. According to findings of the research, the underweight student rate was 11.9% (girls: 6.1%; boys: 5.8%), overweight student rate was 9.1% (girls: 5%; boys: 4.1%) and obese student rate was 8.6% (girls: 5.2%; boys: 3.4%). According to their BMI, 33.3% of underweight students receive dual education, 66.7% full-time education; 47.1% of normal weight students dual education, 52.9% full-time education; 61.8% of overweight students dual education, 38.2% of obese students full-time education; 59.2% of obese students dual education, 40.8% full-time education. A statistically significant relationship was found between the type of education and BMI (p<0.05). As a result, it can be said that the dual education system has increased the rate of obesity. However, the fact that the number of underweight students is higher than the number of overweight and obese students is important for introducing the habits of healthy eating.